Kontribusi Kegiatan Literasi Membaca Dasar, Minat Membaca, dan Kebiasaan Membaca Terhadap Kemampuan Membaca Siswa - Yulistio, Didi; Gumono; Sulistyawati, Nurwinda (UNIB Press, 2025)
Literacy is the ability to speak and think. Reading ability as one of the important elements of basic literacy skills, is contained in the elements of language literacy. This study aims to analyze the Contribution of Basic Reading Literacy Activities, Reading Interest, and Reading Habits to Students' Reading Comprehension Ability. This study uses a quantitative approach and Descriptive-Correlative method. The population of this study was third semester students of the Indonesian Language Education Study Program, FKIP, Bengkulu University. The research sample used purposive sampling (a sample with a specific purpose) of 33 class A students. Data collection used questionnaire and test techniques. The research instruments were (1) questionnaires to collect data on basic literacy activities, reading interest, and reading habits, with the option of using a five-point scale and (2) tests to collect data on reading comprehension abilities in the form of multiple-choice tests. The research instruments were questionnaires and reading ability tests that had been piloted. The main data analysis technique used multiple regression (R) and the Effective Contribution (SE%) formula to determine the contribution of all variables. The results of the study indicate that there is a positive and highly significant relationship between the independent variables and the dependent variable (R=0.729; F=10.954). With a large Effective Contribution (SE) of Basic Literacy Activities, Reading Interest, and Reading Habits to Students' Reading Ability of 53.1% and the remaining 46.9% is a contribution outside the three independent variables. Specifically, the effective contribution (SE) of the variables (1) Basic Reading Literacy Activities of 45.72%, (2) Reading Interest of 3.65%), and (3) Reading Habits of 3.72%). These results indicate that the large contribution to students' reading ability is not only determined by these three variables but is also determined by other variables. However, the largest effective contribution of the three variables that influence the dependent variable is obtained from the basic reading literacy activity variable.